Evaluation of the Suitability of Mammalian In Vitro Assays to Assess the Genotoxic Potential of Food Contact Materials - Pinter, Elisabeth (Foods, 2020)
Background: Non-targeted screening of food contact materials (FCM) for non-intentionally added substances (NIAS) reveals a great number of unknown and unidentified substances present at low concentrations. In the absence of toxicological data, the application of the threshold of toxicological concern (TTC) or of EU Regulation 10/2011 requires methods able to fulfill safety threshold criteria. In this review, mammalian in vitro genotoxicity assays are analyzed for their ability to detect DNA-damaging substances at limits of biological detection (LOBD) corresponding to the appropriate safety thresholds. Results: The ability of the assays to detect genotoxic effects varies greatly between substance classes. Especially for direct-acting mutagens, the assays lacked the ability to detect most DNA reactive substances below the threshold of 10 ppb, making them unsuitable to pick up potential genotoxicants present in FCM migrates. However, suitability for the detection of chromosomal damage or investigation of other modes of action makes them a complementary tool as part of a standard test battery aimed at giving additional information to ensure safety. Conclusion: improvements are necessary to comply with regulatory thresholds to consider mammalian genotoxicity in vitro assays to assess FCM safety.